Pentacyclic Triterpenes from Cecropia telenitida Can Function as Inhibitors of 11β-Hydroxysteroid Dehydrogenase Type 1 - Catalina Mosquera; Aram J. Panay; Guillermo Montoya (Molecules, 2018)
Plant extracts from the genus Cecropia have been used by Latin-American traditional medicine to treat metabolic disorders and diabetes. Previous results have shown that roots of Cecropia telenitida contain pentacyclic triterpenes and these molecules display a hypoglycemic effect in an insulin-resistant murine model. The pharmacological target of these molecules, however, remains unknown. Several lines of evidence indicate that pentacyclic triterpenes inhibit the 11β-hydroxysteroid dehydrogenase type 1 enzyme, which highlights the potential use of this type of natural product as phytotherapeutic or botanical dietary supplements. The main goal of the study was the evaluation of the inhibitory effect of Cecropia telenitida molecules on 11β-hydroxysteroid dehydrogenase type 1 enzyme activity. A pre-fractionated chemical library was obtained from the roots of Cecropia telenitida using several automated chromatography separation steps and a homogeneous time resolved fluorescence assay was used for the bio-guided isolation of inhibiting molecules. The screening of a chemical library consisting of 125 chemical purified fractions obtained from Cecropia telenitida roots identified one fraction displaying 82% inhibition of the formation of cortisol by the 11β-hydroxysteroid dehydrogenase type 1 enzyme. Furthermore, a molecule displaying IC50 of 0.95 ± 0.09 µM was isolated from this purified fraction and structurally characterized, which confirms that a pentacyclic triterpene scaffold was responsible for the observed inhibition. Our results support the hypothesis that pentacyclic triterpene molecules from Cecropia telenitida can inhibit 11β-hydroxysteroid dehydrogenase type 1 enzyme activity. These findings highlight the potential ethnopharmacological use of plants from the genus Cecropia for the treatment of metabolic disorders and diabetes.